2003
DOI: 10.1079/bjn2002757
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and requirements for calcium and phosphorus in the fast-growing chicken as affected by age

Abstract: Three series of experiments were conducted with fast-growing chickens in order: to evaluate the effects of dietary Ca and P on cholecalciferol metabolism and expression; to determine dietary Ca requirements; to determine dietary P requirements. The results of the first series confirmed previous results on the effects of dietary Ca and P on some variables of vitamin D metabolism and expression, Ca homeostasis and P metabolism in the young chicken (1-to 21-d-old), and extended them to older birds (22-to 43-d-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 23 publications
7
33
1
7
Order By: Relevance
“…The lowest Ca to NPP ratio of 1.14 damaged growth performance of broilers. Birds obtained the greatest BWG and FI at 42 d of age when the Ca to NPP ratio ranged from 2.27 to 2.33 in diets with 1α-OH-D 3 or 25-OH-D 3 as vitamin D. Previous research showed that the high Ca to NPP ratio of 4.0 depressed the BWG and FI of broilers (Li et al, 2012) and the optimal Ca to NPP ratio was 2.0 in broiler diets with vitamin D 3 as the vitamin D source (Bar et al, 2003;Rao et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lowest Ca to NPP ratio of 1.14 damaged growth performance of broilers. Birds obtained the greatest BWG and FI at 42 d of age when the Ca to NPP ratio ranged from 2.27 to 2.33 in diets with 1α-OH-D 3 or 25-OH-D 3 as vitamin D. Previous research showed that the high Ca to NPP ratio of 4.0 depressed the BWG and FI of broilers (Li et al, 2012) and the optimal Ca to NPP ratio was 2.0 in broiler diets with vitamin D 3 as the vitamin D source (Bar et al, 2003;Rao et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The NRC (1994) recommended the Ca and NPP requirements of 10.0 and 4.5 g kg -1 (Ca/NPP = 2.22) in 1-to 21-d-old birds, and 9.0 and 3.5 g kg -1 (Ca/NPP = 2.57) in 22-to 42-d-old broilers. Further research showed that the highest performance and tibia mineralization of broilers were observed at a Ca to NPP ratio of 2.0 (Bar et al, 2003;Rao et al, 2007). These data suggest that the Ca to NPP ratio ranges from 2.0 to 2.6 in broiler diets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As diferenças nas exigências de fósforo disponível entre os sexos podem ser decorrentes da maior eficiência alimentar dos machos em relação às fêmeas, pois apresentaram ganho de peso significativamente mais alto sob deficiência de Pd. Esses resultados estão de acordo com os obtidos por Bar et al (2003) que observaram menor exigência de Pd para o crescimento e deposição de cinzas na tíbia de frangos de corte machos em relação às fêmeas.…”
Section: Resultsunclassified
“…No entanto, os resultados obtidos neste trabalho para a fase de 1 a 28 dias de idade foram próximos, tanto para variáveis de desempenho quanto para os parâmetros ósseos. Os dados obtidos corroboram os encontrados por Bar et al (2003), que verificaram que as exigências em fósforo para ganho de peso e deposição de cinzas na tíbia dos frangos de corte em crescimento são similares. As exigências para máximo desempenho e melhores parâmetros ósseos não seguem, portanto, mesmo padrão e isso pode estar associado à idade e ao potencial genético dos animais.…”
Section: Resultsunclassified